EVALUASI PROGRAM PENDIDIKAN NON FORMAL PADA RUMOH BACA HASAN-SAVVAS DI KOTA LHOKSEUMAWE (PIONIR: JURNAL PENDIDIKAN, 2021)
This study aims to evaluate non-formal education programs at Rumoh Baca Hasan-Savvas in Kota Lhokseumawe because in general, the community reading park is difficult to find in Aceh. This study was conducted to find out how the evaluation of non-formal education program on Rumoh Baca Hasan-Savvas in the evaluation of Context, Input, Process, and Product?. The type of this research is qualitative evaluation research, with phenomenological approach of field study. The sample in this study was the head of the Rumoh Baca Hasan-Savvas institute, the person in charge of the program and the students who were taken at random. Data were collected by observation, interview and documentation. The data collected is analyzed by organizing the data, spelling it into units, synthesizing, arranging into patterns, choosing what is important and learning, and making conclusions. The results of this study indicate that in the evaluation of the context: the goal in eradicating illiteracy and marginalization and the context of the program has been implemented fairly well. In the input evaluation: the age level, the area of residence and the background of the learners vary according to the initial provision of the program, the staff education background on Rumoh Baca Hasan-Savvas 90% is S2, in general the teaching staff has experience in the field so as to provide good service to the participants though still short of teachers, donors who help the implementation of the program in Rumoh Baca Hasan-Savvas come from domestic and abroad but still still need other funding for the future. In Process Evaluation: student recruitment process, program management strategy, learning strategy has been done well enough, schedule of program implementation either literacy activity or creative class have been given to every learner but sometimes still hampered on availability of books for literacy activities as well as materials standard for the creation class, the person in charge of the program is appropriate because it is appointed directly by the head of the institution based on the mature consideration. In Product Evaluation: improved achievements and behavioral changes are increasingly for the better.
Keywords: Program Evaluation; Education; Non Formal; Rumoh Baca Hasan-Savvas.